The ultimate foundation of economic science : an essay on method - Von Mises, Ludwig (Kansas City, Kan. : Sheed Andrews and McMeel, 1978)
This volume was Mises' "ultimate" book in more than one sense. It deals with the most fundamental, elemental, and primary sources of economic science; it is "ultimate" also in being Mises' own last book. This work brought to conclusion a sustained flow of scholarly output that had spanned exactly half a century. This work gives us, in a real sense, the final words of which Mises, economist, philosopher, and lover of liberty, had to deliver himself at the close of his life's work.
Includes index.
rpm 21/06/2017
Loans
Keywords: Economics; Economics $1 (BMethodology.s; Positivism; Dialectical materialism